Experiências políticas de mulheres com a água: organizando relações hidrossociais à luz do feminismo decolonial - Thaís Zimovski Garcia de Oliveira (2023)
This thesis aims to analyze the organization of women's hydrosocial relationships through decolonial feminism in the River Basin Committee of Rio das Velhas. To do so, we follow the following specific objectives: 1) to propose an organizational analysis of the Rio das Velhas Watershed Committee (CBH Rio das Velhas) in the light of decolonial feminism; 2) analyze the self-reports of the women participating in the committee, observing how water appears in their narratives about everyday life and experiences on the committee; 3) point out how the organizational context can influence and be influenced in the production of political subjectivities in the struggle for the decolonization of hydrosocial relations. As a reference, the thesis is structured in three theoretical chapters. Initially, we present an epistemological framework through which administration and organizational studies are inserted in a social and language field. In the second chapter, the objective was to outline an introductory mapping of the organization of waters in Brazil in order to situate the normative scenario of waters from a critical perspective in order to present a theoretical basis for the discussion on the subjectivity between ecology and feminism. In turn, the last theoretical chapter aimed to understand hydrosocial relations in Brazil in the light of decolonial feminism. For this, we initially discuss the relationship between subject and nature, approaching how the production of knowledge starts from an organization which subjugates the feminine and nature as overlapping and worthless elements. In the following subchapter, we seek to delve into the ways in which the organization of knowledge takes place in the Brazilian context based on the imbrications between language and the symbolic field. Finally, in its analytical dimension, the thesis presents four chapters in which we seek to understand the experiences of these women from the perspective of decolonial feminism.